Strategi Implementasi Kearifan Lokal Desa Kenali Lampung Barat yang Adaptif Sesuai dengan Perkembangan Zaman - Rosidah Amini; Annisa Rahman (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
This scientific work is a conceptual article that discusses the preservationof local wisdom management in Kenali Village, Belalau District, West LampungRegency, Lampung Province. The purpose of making this article is to describe andfind out the right management is used to preserve local wisdom in accordance withthe times in the Kenali Village. The method used is the study of literature. Datacollection techniques used in this scientific work are by examining journals, andother sources related to functions, goals and management in preserving andoptimizing the potential of local wisdom in a region. The results of this study showthat Kenali Village is one of the villages in West Lampung Regency whose rulesand life values of the people are guided by the prevailing customary law. However, along with the development of the times, the pattern of settlement and land coverin Pekon Kenali continues to grow and experience changes. The results of the Pekonarea assessment are based on the assessment of various criteria areas in PekonKenali from 1969 to 2013, the results show a number or total score of 41. Thismeans that the area of Pekon Kenali is included in the classification of rehabilitationareas, which requires a specific strategy to continue to preserve local communitywisdom . The solution is to apply the existence of customary law in the villagegovernment system and the application of cultural-based and local wisdomconstituent education to the Kenali Village community.